A nationwide survey of patient problem occurrence across different nursing healthcare sectors - Kieft, Renate (Nurs Open, 2017)
AIM: The aim of this study was to determine the patient problems that nurses encounter in different clinical settings and the extent to which they report being able to influence those patient problems. DESIGN: Exploratory online survey research. METHOD: Data were collected through an online questionnaire. We prepared a 2 × 2 matrix to compare the rate of occurrence against the average level of reported influence. Descriptive statistics were used for the data analysis. RESULTS: A total of 440 nurses working in different settings completed the questionnaire. Nurses report having the most influence on patient problems related to self‐care, mobility and functions of the skin. Nurses experience less influence on problems with voice/speech and the tasks required for participation in work/employment.